Special issue on green and ethical finance - BECK, Thorsten (Institutional Knowledge at Singapore Management University, 2022)
This special issue includes several papers that focus on green and ethical finance. The climate change challenge has raised important questions about the financial sector's role in realizing a carbon-neutral global economy. The global financial crisis also brought critical ethical and governance questions for financial sector actors to the forefront. Such developments have together increased attention to environmental, social and governance (ESG) issues among financial sector practitioners, regulators, and investors. Recently, there has been an increasing focus of finance researchers on issues related to ESG and climate change, reflected also in the increasing number of submissions and published papers in the Journal of Banking and Finance related to these topics.